Chest radiographs in acute respiratory distress syndrome: an Achilles' heel of the Berlin criteria? - Bardají-Carrillo, Miguel; Martín-Fernández, Marta; López-Herrero, Rocío; Priede-Vimbela, Juan M.; Arroyo-Hernantes, Irene; Cobo-Zubia, Rosa; Prieto-Utrera, Rosa; Gómez-Sánchez, Esther; Villar, Jesús; Tamayo, Eduardo (Frontiers in Medicine, 2025)
BackgroundDespite the high mortality and economic burden associated with the acute respiratory distress syndrome (ARDS), the role of chest radiograph (CXR) in ARDS diagnosis and prognosis remains uncertain. The purpose of this study is to elucidate clinical characteristics that distinguish ARDS patients from those without ARDS, especially in patients where CXRs are indicative of ARDS.MethodsSecondary analysis of a prospective observational study with 454 postoperative septic patients under mechanical ventilation (MV). Patients were stratified in two groups depending on whether they met the Berlin criteria for ARDS. Primary outcome was identification of clinical characteristics differentiating patients with ARDS confirmed by CXR from non-ARDS patients. Secondary outcome was 60-day in-hospital mortality of postoperative sepsis-induced ARDS.ResultsOne hundred thirty-nine patients (30.6%) had CXRs compatible with ARDS, although ARDS was confirmed in only 45 patients (9.9%). Emergency surgery (OR 6.6), abdominal source of infection (OR 6.0), pneumonia (OR 8.2), and higher lactate (OR 3.9) were clinical features associated with ARDS development confirmed by CXR. ARDS was an independent risk factor for 60-day mortality (OR 1.8).ConclusionAlthough CXR criteria for ARDS diagnosis could be replaced in future definitions, its importance for ARDS diagnosis should not be underestimated.